Hemorrhagic patterns and their risk factors in patients with moyamoya disease. (12th October 2020) - Zhang, Q.; Zhao, M.; Ge, P.; Liu, X.; Wang, R.; Zhang, Y.; Zhang, D.; Zhao, J.
Abstract : Background and purpose: The aim was to describe the profiles of hemorrhagic patterns of moyamoya disease (MMD) and analyze the risk factors in a large population. Methods: A total of 335 conservatively managed MMD patients with hemorrhage in our hospital were included in this cross‐sectional study. The correlation between clinical and angiographic characteristics and hemorrhagic patterns (anterior or posterior hemorrhage) was assessed in the hemorrhagic hemisphere by univariate and multivariate logistic regression models. In addition, stratified analysis was performed. Results: The 335 hemorrhagic hemispheres (patients) comprised 179 (53.4%) anterior and 156 (46.6%) posterior hemorrhages. For all cases, age at onset [odds ratio (OR) 0.98; 95% confidence interval (CI) 0.96–1.00; P = 0.048] and choroidal anastomosis (OR 1.87; 95% CI 1.19–2.94; P = 0.007) were found by multivariate regression analysis to be negatively and positively associated with a significantly increased risk of posterior hemorrhage, respectively. After stratified analysis, hypertension (OR 0.37; 95% CI 0.14–0.97; P = 0.043) was identified by multivariate regression analysis as a risk factor for anterior hemorrhage in patients without dilation of choroidal anastomosis. On the other hand, choroidal anastomosis (OR 2.62; 95% CI 1.02–6.72; P = 0.045) and involvement of the posterior cerebral artery (OR 3.39; 95% CI 1.20–9.63; P = 0.022) were associated with significantly increased risk of posterior hemorrhage in children and young adults (<30 years of age). Conclusions: A dynamic change in hemorrhagic patterns in MMD patients with increasing age at onset was observed. Choroidal anastomosis is a predictor of posterior hemorrhage. Hypertension is a risk factor for anterior hemorrhage in patients without extreme dilation of choroidal anastomosis.